Adsorption Behavior of Iodine by Novel Covalent Organic Polymers Constructed Through Heterostructural Mixed Linkers - Guan, Heda; Zou, Donglei; Yu, Haiyang; Liu, Meijun; Liu, Zhi; Sun, Wentian; Xu, Feifan; Li, Yangxue (Frontiers in Materials, 2019)
The efficient capture and storage radioactive iodine (129I or 131I) formed during the extensive use of nuclear energy is of paramount importance. In this work, we presented a novel covalent organic polymer (JLUE-COP-3) constructed through heterostructural mixed linkers with perforated porousness, plenty of π-conjugated phenyl rings and functional –CO–NH– and –SO3H groups to iodine adsorption process. After fully characterizing the morphology and structure, the adsorption behavior of iodine by the resultant polymers were explored in detail. The external adsorption behavior was determined to obey the pseudo-second order kinetic model according to the kinetic analysis. The maximum liquid adsorption capacity was obtained to reach 153.85 mg/g at 298 K, which was evaluated by the Langmuir isotherm model. In addition, the negative attributes of ΔGo as well as the positive attributes of ΔHo and ΔSo at three temperatures, indicated the nature of the iodine adsorption over JLUE-COP-3 was spontaneous and endothermic.